(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Style is the embodiment of a writer’svision. As David Lodge aptly asserts, “…not a decorative embellishment uponsubject-matter, but the very medium in which the subject is turned into art…”(Biswal P.116). Narayan’s style embodies the Malgudi life not only in terms ofa distinct regional flavour but also in terms of revolts and reconciliations.Narayan adopts the simple style of a storyteller. Events flow naturally, oneout of another, in the same way as they would actually happen in life. Eventshappen and characters live in innumerable equations of human relationships. Toborrow phrases from Wayne C. Booth’s “The Rhetoric of Fiction” it can be saidthat Narayan ‘shows’ but does not ‘tell’ (Biswal P.116). Narayan could havewell said what the young novelist, whom Mr. Booth quotes, says,